Differences in beta-lactam and penicillin allergy: Beyond the West and focusing on Asia-Pacific - Hugo W.F. Mak; Maegan H.Y. Yeung; Jane C.Y. Wong; Valerie Chiang; Philip H. Li (Frontiers in Allergy, 2022)
Beta-lactam (BL) antibiotic “allergy” labels are common, but often overdiagnosed. Although much research has been focused on the BL allergy and the delabelling process in the West, studies from other parts of the world remain sparse. This review outlines the contrasting global epidemiology, shifting clinical practices and disparities of BL allergy in the Asia-Pacific region compared with the West. Innovative strategies to overcome barriers in BL allergy workup are discussed and potential directions for future research and service development are also proposed.